Electrochemical Sensors, a Bright Future in the Fabrication of Portable Kits in Analytical Systems - Karimi‐Maleh, Hassan; Karimi, Fatemeh; Alizadeh, Marzieh; Sanati, Afsaneh L. (Chemical record, 2020)
Analysis of food, pharmaceutical, and environmental compounds is an inevitable issue to evaluate quality of the compounds used in human life. Quality of drinking water, food products, and pharmaceutical compounds is directly associated with human health. Presence of forbidden additives in food products, toxic compounds in water samples and drugs with low quality lead to important problems for human health. Therefore, attention to analytical strategy for investigation of quality of food, pharmaceutical, and environmental compounds and monitoring presence of forbidden compounds in materials used by humans has increased in recent years. Analytical methods help to identify and quantify both permissible and unauthorized compounds present in the materials used in human daily life. Among analytical methods, electrochemical methods have been shown to have more advantages compared to other analytical methods due to their portability and low cost. Most of big companies have applied this type of analytical methods because of their fast and selective analysis. Due to simple operation and high diversity of electroanalytical sensors, these types of sensors are expected to be the future generation of analytical systems. Therefore, many scientists and researchers have focused on designing and fabrication of electroanalytical sensors with good selectivity and high sensitivity for different types of compounds such as drugs, food, and environmental pollutants. In this paper, we described the mechanism and different examples of DNA, enzymatic and electro‐catalytic methods for electroanalytical determination of drug, food and environmental compounds. In present review, we have focused the discussion on the electrochemical‐based analytical sensors as a new and powerful strategy for determination of pharmaceutical, food, biological and environmental compounds. Moreover, we also have discussed the recent advancements in the different types of electroanalytical sensors as portable kits in real sample analysis. Due to high selectivity and good sensitivity, the electroanalytical sensors showed high performance ability and bright future in the fabrication of portable kits. in analytical systems